SINERGI LITERASI KEUANGAN DAN KESEHATAN DALAM PEMBERDAYAAN PEREMPUAN UNTUK KESEJAHTERAAN KELUARGA - Diany, Adista Anjar; Surya Ayu Pertiwi; Aulia Helmina Putri; Nico Kosasih; Rifqi Amrulloh; Tina Lestari; Ernawati (Universitas Kadiri, 2025)
This community service program aims to strengthen the role of women in building a healthy and independent community by providing material on cancer prevention and family financial literacy. The target audience for this program is members of the PIKK (Persatuan Istri Karyawan Karyawati) PT. PLN Nusantara Power Pulang Pisau. The activities utilize digital technology integration through interactive webinars via Zoom using a Participatory Action Research (PAR) approach. Evaluation was conducted through several approaches, including: Pre-Test and Post-Test, Participant Satisfaction Questionnaire, In-Depth Interviews, and Focus Group Discussions (FGD). The education provided not only impacts individuals but is also expected to spread to families and surrounding communities, thereby forming a more resilient community capable of facing future health and economic challenges.